Microwave attenuation (10GHz) of the Oxidized polymer membranes surfaces - Yahya Al-Jammal; Theyaa Al-Taee (College of Education for Pure Sciences, 2005)
In this research , microwave ray absorbing coating materials had been prepared which work within ( X - band ) frequency i.e 3 cm wavelength . The coating materials were prepared from a mixture of pigmented materials such as metals oxides , carbon black and binding materials such as epoxy or unsaturated polyester . The absorbitivity value for the prepared sample of mixing ratio 4% and by using epoxy as binding for the oxides , MgO , A12O3 , ZnO , FeO and carbon black ( C ) were 26.9% , 23.4%, 15.9%, 15.5% and 22.6% respectively. Moreover, it was found the absorbitivity values of the same ratio for the prepared sample mixture of ( MgO + A12O3 + C )and( MgO + Si02 + C ) and their thickness ( 0.95mm ) were by using epoxy as binding , 28.1 % and 29.6% . However , we have found these values , did not change a lot as changing the binding polymer material (i,e epoxy or the unsaturated polyester) . We have interpreted the variance changing in absorbitivity value for all samples under study to the electronegativity for 'oxides , so whenever its value was for one oxide or the difference between any two oxides is big , so the absorbitivity values would be big also . It had been taken into consideration in the sample prepared from (MgO + SiO2 + C ) because of great difference in electronegativity. So we noticed that the absorbitivity values increases as both of the mixture weight . The thickness increases at 4% mixing ratio , So when the mixture weight per unit area was(0.14 gm/cm2) and thickness of ( 1 ,0mm) , the absorbitivity was( 29.6%) with when the mixture weight per unit area was( 0.21 gm/cm2 ) and thickness of ( 1.5mm) ,The absorbitivity was ( 61.24% ) , but at weight per unit area was ( 0.28 gm/cm2 )with thickness of ( 0.21mm) the absorbitivity value became ( 73.1%) ,